Perubahan Faktor Keausan Die Drawn UHMWPE Akibat Tegangan Kontak untuk Aplikasi Sendi Lutut Tiruan - Jefri S. Bale (Institute of Research and Community Outreach, Petra Christian University, 2009)
The aim of this research is to study the effects of contact stress on the wear of die drawn UHMWPE GUR 1120 against nitrogen ion implanted cobalt chrome alloy used pin on plate unidirectional reciprocating movement wear test. A constant load was applied to each UHMWPE pin to produce a contact stress, whereas the contact stress was varied of 5 MPa, 9 MPa and 12 MPa with constant sliding velocity of 116.5 mm/s. The result shows the wear factor decreasing with increasing contact stress. The lowest contact stress (5 MPa) gives the highest wear factor that is: 2.67x10-7 mm3/Nm. The different wear factor is caused by increasing contact stress changed wear mechanism of surface contact. The lowest contact stress dominated by abrasive wear mechanism while along increasing contact stress changing the dominate wear mechanism into burnishing wear mechanism and also surface deformation wear mechanism. Abstract in Bahasa Indonesia: Penelitian ini bertujuan untuk mengetahui pengaruh tegangan kontak terhadap faktor keausan die drawn GUR 1120 UHMWPE berpasangan dengan cobalt chrome alloy yang diimplantasi ion berbasis nitrogen menggunakan pin on plate unidirectional reciprocating movement wear test. Pin die drawn UHMWPE dibebani sehingga menghasilkan tegangan kontak berkisar 5 MPa, 9 MPa dan 12 MPa dengan kecepatan gesekan konstan 116,5 mm/dtk. Dari hasil penelitian yang telah dilakukan, disimpulkan bahwa faktor keausan UHMWPE akan menurun seiring dengan meningkatnya tegangan kontak. Tegangan kontak terkecil (5 MPa) menghasilkan faktor keausan rata-rata UHMWPE yang terbesar yaitu 2,67x10-7 mm3/Nm. Perbedaan nilai faktor keausan ini disebabkan karena peningkatan tegangan kontak merubah mekanisme keausan pada permukaan kontak. Tegangan kontak terkecil di dominasi mekanisme abrasive wear sedangkan seiring peningkatan tegangan kontak mekanisme keausan didominasi oleh burnishing wear mechanism serta adanya mekanisme surface deformation wear. Kata kunci: Faktor keausan, tegangan kontak, die drawn UHMWPE, cobalt chrome alloy, implantasi ion nitrogen.